Genetic variation for seed yield and its components and their association in coriander (Coriandrum sativum L.) germplasm - V Khandelwal, K N Shiva, Dhirendra Singh, U K Jain, S S Rajput (Journal of Spices and Aromatic Crops, 2006)
Evaluation of 360 lines of coriander (Coriandrum sativum) at Jobner (Rajasthan) indicatedhigh variability for seed yield (22.82%), umbels plant-1 (28.65%) and seeds umbel-1 (21.63%)and low variability for days to 50% flowering (12.39%) and umbellets umbel-1 (13.30%). Highbroad sense heritability (91.94%) and genetic advance (56.55%) were obtained for umbelsplant-1 and seeds umbel-1. Correlation and path coefficient analysis indicated that umbelsplant-1 and branches plant-1 were the most important traits as they exerted positive directeffect on seed yield.